Of societal depravity: existentialism, realism and contrapuntal criticism in Nigerian arabic poetry: Ibn Yusuf’s anthology as a paradigm (2023)
The intrinsic nexus between man and society is apparently oblivious and impervious to many people despite the huge quantum that circumvented its basic responsibilities and immense rotes in society. The paradoxical attitudes of man in engaging in social vices and illicit characters have given birth to decay in society. However, social change or sociocultural evolutions might be necessary to restore normalcy and social Order. Nigerian Arabic poets since the 19th Century have engaged in utilizing their poems for social change through socio-cultural, religious-economic, scientific or technological forces. The theoretical framework in this paper will be examined through the Heraclitan model, which is parallel to that of a living organism. That is, in Order to remain alive, there must be constant changes. A Contemporary application of this approach is shown in the social- change theory called seed-scale, which builds up the complexity theory as a subfield of emergence. Therefore, the thrust of this paper is to examine the societal depravity as elucidated in Ibn Yusufs anthology and proffers a contrapuntal criticism of it. Before delving into the main discussion, the paper examines the concepts of existentialism and realism as a philosophical interface. Likewise, the issues of man and social change and an Overview of Nigerian Arabic poetry are discussed. Ibn Yusufs biography, scholarship and the review of his anthology are also studied. The paper concludes by critically examining contrapuntal criticism of societal depravity through Ibn Yusufs anthology.